Skarnawalizowany świat „Tajemnicy lorda Singelworth” - Kuffel, Julia (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
The article is an attempt at reading Norwid’s Tajemnica lorda Singelworth (Lord Singelworth’s secret) in the light of Mikhail Bakhtin’s carnival theory. This novella exhibits three constitutive traits of the “seriousness-laughter” literature, which the carnivalesque literature stems from, as well as a number of characteristics of Menippean satire considered by Bakhtin to be the most representative genre of this literary movement. In the article, the author demonstrates that the novella also shows other features of Menippean satire presented in Bakhtin’s theory. This is followed by an analysis of the jester character, Tonin di Bona Grazia, who stands in opposition to the titular character, and by a reflection on Venice – the carnival city – and the city’s significance to deciphering the meanings hidden in the novella. These analyses support the hypothesis that Tajemnica lorda Singelworth exhibits characteristics traits of carnivalesque literature.